Payoffs to a half century of CGIAR research - Alston, Julian; Pardey, Philip G.; Rao, Xudong (Wiley, 2022)
The CGIAR is a unique and highly successful institutional arrangement for funding and conducting multilateral agricultural R&D. Established in 1971, the CGIAR has spent about $60 billion in present value terms mainly on R&D for staple food crops to support the world's poor. In this study, we provide a quantitative assessment of the past payoffs to CGIAR research. We compiled a comprehensive set of all known studies reporting estimates of returns to CGIAR research and to public research undertaken by low‐ and middle‐income countries. We transformed these rate of return estimates into standardized benefit–cost ratios (BCRs), and we conducted a statistical meta‐analysis. As a robustness check, we also undertook two complementary assessments. These comprised a selective review of nine (“billion‐dollar”) studies reporting large‐scale benefits to CGIAR investments and an approximation approach based on an attribution of total factor productivity growth. The results are remarkably similar across the methods. All the evidence points to an overall BCR on the order of 10:1 across the portfolio for past CGIAR research investments.